Synthesis, physical properties, and root canal sealing of experimental MTA- and salicylate-based root canal sealers. - Rafael Pino Vitti; Kusai Baroudi; Tarun Walia; Raghavandra M Shetty; Flávia Goulart da Rosa Cardoso; Flávia de Moura Pereira; Evandro Piva; Cesar Henrique Zanchi; Gabriel Flores Abuna; Carolina Oliveira de Lima; Emmanuel João Nogueira Leal Silva; Flávio Henrique Baggio Aguiar; et al. (PLoS ONE)
Objectives To develop and evaluate the physical properties and sealing ability within the root canal of three experimental sealers based on MTA and a salicylate resin. Materials and methods The experimental sealers were composed of two pastes. The base paste was prepared using 1,3-butyleneglycol disalicylate and bismuth oxide. Three different catalytic pastes were formulated, creating three groups: [MTA] n,n,dihydroxyethyl-p-toluidine (DPT), titanium dioxide (TiO2), and mineral trioxide aggregate (MTA); [MTA-HA] DPT + TiO2 + MTA + hydroxyapatite (HA); and [MTA-DCPD] DPT + TiO2 + MTA + dibasic calcium phosphate dihydrate (DCPD). MTA Fillapex (Angelus) was used as the commercial reference (control). The sealers were manipulated at a 1:1 ratio (base paste:catalyst). Tests for working time and setting time, flow, and film thickness were conducted following ISO 6876:2012 standards. Single-rooted human teeth root canals were utilized for evaluating root canal filling using micro-computed tomography, push-out bond strength testing, and sealer penetration into dentinal tubules using confocal microscopy. Failure patterns in the push-out test were classified as adhesive, cohesive, or mixed. Sealer micromorphology was analyzed via scanning electron microscopy. Data were analyzed statistically (α = 0.05). Results MTA Fillapex showed the longest working and setting times, highest flow, the lowest film thickness, and better penetration into dentinal tubules. There was no difference in void among evaluated sealers. Overall, MTA-DCPD sealer showed the lowest bond strength values for cervical and apical thirds. Micromorphological analysis revealed similar crystallographic properties among all sealers. Conclusions The sealers tested showed reduced working and setting times, with flow and film thickness according to ISO 6876:2012. Their void volume and bond strength were similar to MTA Fillapex, except for MTA-DCPD. Clinical Relevance: The experimental root canal sealers demonstrated suitable physical properties and good adaptation within the root canal.